Alice's adventures in wonderland ; &, Through the looking-glass - Carroll, Lewis, 1832-1898.; Meyers, Jeffrey; Tenniel, John, Sir, 1820-1914.; Gardner, Martin, 1914-2010. (New York : New American Library, 2012)
A little girl falls down a rabbit hole and discovers a world of nonsensical and amusing characters.
Alice's adventures in Wonderland -- Through the looking-glass.
Includes bibliographical references.
3-6
Keywords: Alice -- (Fictitious character from Carroll) -- Fiction; English fiction -- 20th century; Fantasy literature, English; Fantasy; Fantasy fiction